VIBRATION ANALYSIS AND FAULT DIAGNOSIS OF VERTICAL (ROTARY TABLE) INSERT- MOULDING MACHINE AND PRESS MACHINE (WITH FEEDER) - Omkar Pawar1, Dhondiram Waghmode2, Nanasaheb Shinde3, Dnyaneshwar Shitole4, Sandipraj Salunkhe,5 Vidyanand Jakukore 6 (International Journal of Innovations in Engineering Research and Technology, 2022)
Molding is the process of turning raw plastic into a shape or form that is the desired finished product. Every kind of product demands a different molding technique, and among them, overmolding process and insert molding design types are considered the best molding techniques in the market. The conventional plastic manufacturing process involves melting or softening the plastic at considerably high temperatures and then using different techniques to mold them into shapes that make them a useful finished product. Molding is used in making virtually any moulded component out of plastic following design considerations for plastic overmolding. A plastic chair or anything made out of plastic is basically made using molding techniques. In this blog post, we will discuss insert molding various design aspects related to the technique in detail. The aim of this post is to discuss the most common and encouraged molding technique in the world (insert molding), its working methodology, design considerations, benefits and applications in various sectors. These types of failures might take place during the manufacturing process and therefore it is important to review the problem and monitor the condition of vertical insert- moulding machine, so that the details of failure would occur before any harsh consequences take place. Therefore, an early detection and indication is necessary for the safety and reliability of machine. This paper describes various vibration monitoring techniques suitable to analyze the defect in vertical insert- moulding machine. By performing this test, these techniques would reveal information about the progressing faults. From the different maintenance techniques, conditioning monitoring which is one of the techniques is highlighted. It uses the vibration having high frequencies which are generated from faulty components, is therefore investigated and compared. From the different conditioning monitoring techniques, vibration analysis method is been elaborated and therefore utilized as a medium to fulfill the aim. An experimental set up is used to testify and investigate good parts and faulty parts by using different measurement tools pulse software, visteck analyzer to measure amplitude, sensors to obtain faulty signals. Also, the vibration signatures caused due to damages at moving parts are examined. The result indicates that faulty parts have a strong effect on vibration spectrum. This paper therefore reveals frequencies domain signals from vibration analysis. Overall, this paper has demonstrated that different techniques are useful in detecting the problems in insert -moulded machine components.